The literal association phenomenon within the scope of Arabic linguistics - Abdurahman Almuways, Yasir Sulaiman; Elatrash, Radwan Jamal Yousef (IIUM Press, International Islamic University Malaysia, 2019)
This article highlights the Phenomenon of the Literal Association (Ẓāhirat al-Mushtarak al-Lafẓī) within the field of Arabic Linguistics in which the perspectives of the classical and modern scholars of Arabic Linguistics are viewed, analysed, and evaluated in order to reach the conclusion of whether or not such a linguistic phenomenon exists. The theory of this research is based on the analytical research methodology and inductive research methodology, which will employ both the quantitative and qualitative approaches by which we explore the definition of the literal association in the Arabic language, the opinions and disputes of scholars of the Arabic language about the existence of literal association in the Arabic language, the factors and the reasons behind the emergence of literal association in the Arabic language, and the factors by which the semantics of the literal association can be determined in the Arabic language.